Fermented sorghum porridge fortified with moringa leaf powder for physical growth in stunted children in East Nusa Tenggara, Indonesia - Cahyani, Sisilia Leny; Bedho, Marthina; Kurnia, Theresia Avila (Malahayati International Journal of Nursing and Health Science, 2024)
Background: East Nusa Tenggara is one of the provinces in Indonesia that has a higher stunting problem compared to other provinces. This value is a contribution to the prevalence of stunting in various districts in East Nusa Tenggara, one of which is Ende District. Currently, East Nusa Tenggara Province is promoting the use of moringa and sorghum plants for re-cultivation as substitutes for rice and corn.Purpose: To find out the effect of giving sorghum and moringa cookies on the growth and development of stunted children in Ende Regency.Method: This research uses a quasi-experimental type of research with a one group pretest-posttest design. Carried out in the work area of the Ende Regency, research was conducted from 2 August-3 September 2021, totaling 96 people sampling was carried out using non-probability sampling so that the total was 55 people. The independent variable in this study was consumption of cookies made from sorghum and moringa, while the dependent variables were height, body weight, and upper arm circumference. The instruments used in this research were interview guides, observation sheets, and tools for measuring height, weight, and upper arm circumference.Results: This research states that there is an effect of increasing height, weight, upper arm circumference in stunted children when given cookies sorghum and Moringa leaves because there is an increase after being given the intervention.Conclusion: Providing sorghum and moringa has an effect on the growth and development of stunted children in Ende Regency.Suggestion: Public health centers can provide education regarding providing additional food to stunted children by providing local foods such as sorghum and moringa. Meanwhile, the Regional Government of Ende Regency should encourage sorghum cultivation more massively.